ASUHAN KEPERAWATAN PADA KLIEN GASTRITIS DENGAN PENURUNAN ASUPAN NUTRISI DAN GANGGUAN POLA TIDUR - Alya Rachmmawati (2023)
Introduction: gastritis is a disease that interferes with the digestive system where there is inflammation in the lining of the stomach wall, classified into acute and chronic. Symptoms that are felt are bloating, frequent belching, nausea and vomiting, to loss of appetite, and cause abdominal pain. Writing scientific papers is done in order to be able to analyze the application of nursing care to Mrs. D with Gastritis including nursing assessment, nursing interventions, nursing implementation and nursing evaluation. The writing design in this scientific paper is descriptive using the case study. method: With 1 elderly female respondent with a medical diagnosis of gastritis. Results Analysis: nursing problems that arise in cases, namely the risk of nutritional deficits associated with psychological factors characterized by reluctance to eat and the presence of disturbed sleep patterns associated with lack of control over sleep after 3 visits to the results of the evaluation of nursing diagnoses risk of nutritional deficits associated with marked psychological factors with the reluctance to eat it has been resolved while sleep pattern disturbances related to lack of sleep control are resolved partly because the 5 finger hypnosis therapy that is applied is not used to the client doing it independently and still needs guidance. Conclusion: the application of nursing care to Ny.D with Gastritis achieves results that are in line with expectations with a relationship of mutual trust and clients and students can take action according to mutual agreement.